Understanding of Creed-Related Hadiths in the Book Tuhfat al-Raghibin by Sheikh Muhammad Arsyad al-Banjari - Hanafi, Hanafi (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
This study examines the unique approach of Sheikh Muhammad Arsyad al-Banjari in understanding and interpreting creed-related Hadiths in his book Tuhfat al-Raghibin. Al-Banjari, not primarily known for his work in Hadith scholarship, leverages his authoritative knowledge in other Islamic disciplines to offer fresh insights into Hadith interpretation. Employing qualitative research methodology, the study conducts a discourse analysis of Tuhfat al-Raghibin. This involves a detailed examination of the content and textual nuances to understand al-Banjari’s interpretive patterns. The research reveals that al-Banjari's interpretations of Hadiths in Tuhfat al-Raghibin are predominantly influenced by Asharite theology, al-Maturidiyyah, and Shafi'i jurisprudence. His methodological blend contributes to the theological development of Ahl al-Sunnah wa al-Jama'ah, especially in transitioning the religious beliefs and practices of a community from animism-dynamism to monotheism. The findings highlight the significance of al-Banjari's methodology in understanding and applying Hadiths in Islamic law. His approach underscores the need for a balanced interpretation of Hadiths, taking into account historical, social, and contextual factors. The study broadens the understanding of Hadith interpretation and its implications for Islamic jurisprudence